The handbook to IFRS transition and to IFRS U.S. GAAP dual reporting : interpretation, implementation and application to grey areas - Bellandi, Francesco (Chichester, West Sussex : John Wiley, 2012)
An indispensable guide to making the transition to dual IFRS/GAAP financial reporting. U. S. financial reporting will undergo an unprecedented level of change within the next several years. U.S. companies face a convergence between U.S. GAAP and IFRS, affecting several major accounting standards--most notably in the areas of leasing, revenue recognition, and financial instruments. It is imperative that U.S. companies understand these major changes and their business and operational implications. The IFRS U.S. GAAP Dual Reporting Handbook to First-Time Adoption offers a comprehensive treatment of both the principles and techniques of dual reporting under IFRS/U.S. GAAP, while exploring the practical implications for accounting professionals of reporting under both sets of standards.
Keywords: Financial statements -- Standards -- United States; Accounting -- Standards -- United States